The Role of Communicative Language Teaching (CLT) in Teaching English to Indonesian Elementary School Students within the Kurikulum Merdeka - Ramadhani, Gina; Nidi, Imelda Verista; Zahra, Lailatu (STAIRS: English Language Education Journal, 2024)
English instruction in Indonesian elementary schools continues to face challenges, including limited resources, teacher proficiency gaps, and a reliance on traditional methods. Although Communicative Language Teaching (CLT) presents a promising alternative with its focus on student-centered, interactive learning, its effectiveness in supporting the objectives of the Kurikulum Merdeka requires further investigation. This study investigates the impact of CLT on the instruction of English to primary school children in Indonesia, specifically within the context of the Kurikulum Merdeka. This study employs a qualitative methodology to analyze recent journal articles and investigate how CLT facilitates students' exposure to authentic communication, encourages active engagement, boosts their motivation, and enhances their overall language competency. The results demonstrate that implementing CLT has a significant positive impact on students, as it enhances the relevance and engagement of their learning, aligning with the aims of the Kurikulum Merdeka. The study suggests that to improve English language teaching in Indonesia, it is important to apply the recommendations for broader adoption, integration into the curriculum, development of resources, ongoing evaluation, community involvement, and technology integration.